Funcionarios Oficina de Audiovisuales. (UNED, 2025)
En el orden usual: Héctor Julio Durán, Gerardo López, Eduardo Cordero, Agustín Gámez, Adalberto Blanco, Alejandro Jaén, Abraham Montoya, Sonia Mayela Rodríguez, Adriana Oviedo, Yadira Espinoza, Roberto Román, Susana Arroyo, Raquel Molina Hueso